PEMANFAATAN CELEBRITY ENDORSEMENT DALAM MENUNJANG PENJUALAN PRODUK MOCHICHA BANDA ACEH - Irhamna, Cut Putro; Nurrahmi, Febri; Yanuar, Deni (SOURCE : Jurnal Ilmu Komunikasi, 2025)
Mochicha Bakery is a shop that offers a variety of Mochi cakes and snacks. To promote its products, the business employs several marketing strategies, including celebrity endorsement. This study aims to examine how celebrity endorsement is utilized to support the sales of Mochicha products. The research applies Invitational Rhetoric Theory and uses a descriptive qualitative approach. Informants were selected through purposive sampling and include the owner of Mochicha Bakery Banda Aceh, the celebrity involved in the endorsement, and three consumers. Data were collected through semi-structured interviews and documentation of endorsement content. The data analysis follows Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings reveal that the four key endorsement functions (informing, influencing, reminding, and pervasiveness) are present in the celebrity’s promotional content, with "informing" being the most dominant. Additionally, the celebrity meets the characteristics of effective endorsers: visibility, credibility, attractiveness, and power. The study concludes that celebrity endorsement effectively supports Mochicha Bakery’s sales, primarily through a soft-selling approach that subtly attracts consumers via the celebrity’s unique style and personal branding.